Response to “An exceptionally preserved 110 million years old praying mantis provides new insights into the predatory behaviour of early mantodeans” - Sydney K. Brannoch; Gavin J. Svenson (PeerJ, 2017)
Hörnig, Haug & Haug (2017) published a description of a new specimen of Santanmantis axelrodi MB.I.2068, an extinct species of praying mantis from the Crato Formation of Brazil. According to Hörnig, Haug & Haug (2017), the discovery of this new specimen brought with it implications for praying mantis character evolution and predatory behavior; it is with these lines of reasoning that we find fault. More specifically, we point to four flawed assumptions in their study that led to their unsubstantiated conclusion that S. axelrodi employed their mesothoracic legs in prey capture.